Pragmatic and contextualized methods selection for safety assessment of infant systemic exposure through human milk: the Milk4baby decision tree approach - a contribution from the concePTION project - Monfort, Anaëlle; Macente, Julia; Van Neste, Martje; Huang, Miao-Chan; Nauwelaerts, Nina; Abza, Getahun Befirdu; Winterfeld, Ursula; Smits, Anne; Allegaert, Karel; Annaert, Pieter; Guidi, Monia; Panchaud, Alice (Frontiers in Pharmacology, 2025)
More than 50% of women take at least one medication during lactation. However, 54% of drugs in the LactMed database lack lactation safety data, and only 2% have robust evidence. This highlights a significant gap in guidance for designing pharmacokinetic and safety studies characterizing infant safety following medication exposure during lactation, despite FDA guidelines recommending clinical lactation studies. Additional guidance is needed to select the most suitable study design for these studies. To address this, we identified key medication-related characteristics essential for designing lactation studies that assess infant safety following systemic exposure during lactation. This allowed us to develop a decision tree, named Milk4baby, to guide researchers in selecting the most appropriate methodological approach for each medication. Milk4baby was designed by reviewing the literature and iterative discussions with an interdisciplinary panel of experts in clinical pharmacology, lactation, and pharmacometrics on factors influencing the selection of the methodological approach and design of a lactation study. The decision tree first considers the prevalence of medication utilization in women of childbearing age. Next, the medication’s safety profile in infants aged 0–2 years must be assessed using available safety data from infants, adults, and/or animals. Finally, the expected infant systemic exposure level is evaluated based on medication’s oral bioavailability, transfer into human milk, risk of accumulation, and utilization patterns. After completing these steps, the decision tree recommends the most suitable methodological approach including case reports/case studies, population pharmacokinetic (popPK) modeling, physiologically based pharmacokinetic (PBPK) modeling and simulations, or pharmacoepidemiologic studies. Verification of the decision tree on 50 randomly selected medications from the LactMed and Le CRAT databases revealed that PBPK and case reports were the most appropriate approaches in 29 cases, primarily due to low prevalence of medication utilization. Designing popPK, PBPK, or pharmacoepidemiologic studies can be time-consuming and resource-intensive, while poorly designed case reports/case studies may yield limited or misleading information. Therefore, Milk4baby aims to help researchers enhance the efficiency and accuracy of determining infant safety following systemic exposure during lactation by choosing the most suitable strategy for lactation studies, ultimately supporting better-informed decisions for lactating women and their healthcare providers.